Analisis Pengaruh Ukuran Perusahaan, Leverage dan Profitabilitas Terhadap Nilai Perusahaan: Studi Kasus Sub Sektor Transportasi dan Logistik Periode 2021-2023 - Zebua, Seprianto; Nuswandari, Cahyani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to test the significant influence of company size, leverage and profitability on company value. This research was conducted on Transportation and Logistics companies listed on the IDX for the 2021-2023 period. The approach used in this research is quantitative. The population in this study was 112 companies listed consecutively on the IDX from 2021-2023. Sampling used a purposive sampling method and a sample of 68 companies was obtained. Data analysis techniques used in this research include descriptive analysis, normality test, classical assumption test and research model testing. The results of the hypothesis test show that company size has a negative effect on company value. Leverage has a positive effect on company value. Profitability has no effect on company valueKeywords: Company Size, Leverage, Profitability, Company Value.